Survival of malignant mesothelioma and other rare thoracic cancers in Germany and the United States: A population‐based study. Issue 6 (3rd March 2020) - Sirri, Eunice; Kieschke, Joachim; Vohmann, Claudia; Katalinic, Alexander; Nennecke, Alice; Ressing, Meike; Eberle, Andrea; Holleczek, Bernd; Jansen, Lina; Brenner, Hermann
Abstract : Evidence on survival of malignant mesothelioma (MM) and other rare thoracic cancers is limited due to the rarity of these cancer sites. Here, we provide a comprehensive overview of MM incidence and survival after MM and other rare thoracic cancers in Germany and the United States (US). Incidence was estimated from a German National Cancer Database and from the Surveillance, Epidemiology and End Results (SEER) 18 database for 2000–2014. Patients diagnosed in 1997–2013 with malignant epithelial tumors of the trachea (Etra), epithelial tumors of the thymus (Ethy) and MM were extracted from a German cancer survival database and from the SEER 13 database. Period analysis was employed to compute 5‐year relative survival (RS). During 2000–2014, an annual average of 0.9 and 0.6 MM cases per 100, 000 person‐years was diagnosed in Germany and the US. Rates decreased in Germany and in the US. Patients with Ethy had highest 5‐year RS with US patients surviving longer (69.1% compared to 63.7%, p = 0.02). Survival after Etra was comparable in both countries (Germany 33.6%, US 34.4%, p = 0.07). Survival in MM patients was poor overall (Germany 11.8%, US 12.1%, p < 0.01). Survival improvements were only observed in MM patients in Germany (10.8% [2002–2007] vs. 13.0% [2008–2013], p < 0.01). The lack of progress in survival for Etra and Ethy patients underlines the need of novel preventive, therapeutic and diagnostic approaches. MM incidence significantly decreased in Germany and in the US. Further monitoring of MM incidence is warranted given that a peak in incidence is expected in 2020–2030 in Western countries. Abstract : What's new? Certain cancer types that originate from the epithelial or mesothelial tissues of the thoracic cavity are exceedingly rare. As a consequence, little is known about their incidence and survival. Here, utilizing national databases, the authors estimated incidence and survival of malignant mesothelioma (MM) and other rare thoracic cancers in Germany and the United States. Analyses show that between 2000 and 2014, MM incidence declined in both countries, although only MM survival improved in Germany. No improvements were observed in either country for survival of epithelial tumors of the trachea and thymus, highlighting a need for preventive and therapeutic advances.